Daidzein is the in vivo active compound of Puerariae Lobatae Radix water extract for muscarinic receptor-3 inhibition against overactive bladder - Qiang, Yining; Bai, Lu; Tian, Shuran; Ma, Yi; Xu, Pingxiang; Cheng, Mingchang; Wu, Yi; Li, Xiaorong; Xue, Ming; Zhou, Xuelin (Frontiers in Pharmacology, 2022)
BACKGROUND In the previous study, Puerariae lobatae Radix (named Gegen in Chinese) water extract attenuated M3 receptor agonist carbachol-induced detrusor contraction after 3-week oral administration in a hypertension-associated OAB (overactive bladder) model. This research aimed to investigate the active ingredients from Gegen water extract against OAB. METHODS Bioassay-guided fractionation was performed by using preparative HPLC for fast isolation of fractions followed by screening their ex vivo activity through carbachol-induced bladder strip contraction assay. Chemicals in each active fraction were analyzed by HPLC-UV. In vivo urine metabolites were quantified by LC-MS/MS after sub-acute administration. Thermal shift assay with recombinant human M3 receptor protein was performed and molecular docking analysis was used for molecular modelling of M3 receptor inhibition. RESULTS Bioassay-guided fractionation results for isolating M3 receptor inhibitors indicated that four compounds were identified as active ingredients of Gegen water extract, and their inhibition potency on carbachol-induced detrusor contraction was ranked in descending order according to their inhibition concentrations as followed: genistein > daidzein > biochanin A >> puerarin. Daidzein in urine reached ex vivo effective concentration to inhibit detrusor contraction, but others did not. Daidzein concentration-dependently increased the melting temperature (Tm) of recombinant human M3 receptor protein with a positive binding (ΔTm = 2.12 oC at 100 μg/mL). Molecular docking analysis showed that daidzein can potently bind to the ligand binding pocket of the M3 receptor via hydrogen bond. CONCLUSION Puerarin and its derivatives were pro-drugs, and daidzein was their in vivo active form via M3 receptor inhibition for treating OAB.